Professionally-oriented model of long-term sports training of football play - Lavrichenko, V. V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to theoretically substantiate the stages of a professionally oriented model of long-term sports training of football players from the standpoint of increasing their competence in competitive activities.